Inspiratory muscle conditioning exercise and diaphragm gene therapy in Pompe disease: Clinical evidence of respiratory plasticity - Smith, Barbara K.; Martin, A. Daniel; Lawson, Lee Ann; Vernot, Valerie; Marcus, Jordan; Islam, Saleem; Shafi, Nadeem; Corti, Manuela; Collins, Shelley W.; Byrne, Barry J. (Experimental neurology, 2017)
Pompe disease is an inherited disorder due to a mutation in the gene that encodes acid α-glucosidase (GAA). Children with infantile-onset Pompe disease develop progressive hypotonic weakness and cardiopulmonary insufficiency that may eventually require mechanical ventilation (MV). Our team conducted a first in human trial of diaphragmatic gene therapy (AAV1-CMV-GAA) to treat respiratory neural dysfunction in infantile-onset Pompe. Subjects (aged 2–15years, full-time MV: n=5, partial/no MV: n=4) underwent a period of preoperative inspiratory muscle conditioning exercise. The change in respiratory function after exercise alone was compared to the change in function after intramuscular delivery of AAV1-CMV-GAA to the diaphragm with continued exercise. Since AAV-mediated gene therapy can reach phrenic motoneurons via retrograde transduction, we hypothesized that AAV1-CMV-GAA would improve dynamic respiratory motor function to a greater degree than exercise alone. Dependent measures were maximal inspiratory pressure (MIP), respiratory responses to inspiratory threshold loads (load compensation: LC), and physical evidence of diaphragm activity (descent on MRI, EMG activity). Exercise alone did not change function. After AAV1-CMV-GAA, MIP was unchanged. Flow and volume LC responses increased after dosing (p<0.05 to p<0.005), but only in the subjects with partial/no MV use. Changes in LC tended to occur on or after 180days. At Day 180, the four subjects with MRI evidence of diaphragm descent had greater maximal voluntary ventilation (p<0.05) and tended to be younger, stronger, and use fewer hours of daily MV. In conclusion, combined AAV1-CMV-GAA and exercise training conferred benefits to dynamic motor function of the diaphragm. Children with a higher baseline neuromuscular function may have greater potential for functional gains. •Children with Pompe disease and ventilatory insufficiency received AAV1-CMG-GAA.•Exercise alone did not change respiratory muscle function in any subjects.•In less-affected children, dynamic respiratory function improved after gene therapy.